Exploring innovation resistance in tourism: barriers to metaverse adoption among tourists - Sowmya G; Aruna Polisetty; Rimjhim Jha; Sarika Keswani (Cogent Business & Management, 2024)
Metaverse is a concept that envisions a future where the physical and digital worlds merge to form a shared space for people to experience and interact with each other. This research aims to study the underlying factors (functional, psychological and individual barriers) that build resistance toward metaverse among tourists. The study has used innovation resistance theory (IRT) to make the conceptual model. The study used a mixed-method approach to investigate the proposed model, with data collected from 26 tourists for qualitative analysis and 198 for quantitative analysis. The data were analysed using structural equation modelling for path analysis. For moderation, the study used process macro model no. 1. The study results showed that the use of metaverse experiences requires certain conditions that increase the cost of usage. Technology vulnerability, characterized by dependence on technology and anxiety about it, was identified as the main cause of innovation resistance also found that people who are not inclined to be innovative or inventive are less likely to embrace new technology and access to better resources, compatible devices, and user-friendly environments can help reduce the barriers that users face in adopting metaverse applications. Tourism, which is mainly related to pleasure and happiness, is strongly influenced by hedonic motivations.
Keywords: 650; metaverse; tourism; innovation resistance; technology vulnerability; passive innovation resistance